Studies Towards the Total Synthesis of Populusone: Stereoselective Construction of Functionalized 2-Oxa-bicyclo[2.2.2]octenes - Hemmersbach, Lars; Schmalz, Hans-Günther (Synlett, 2022)
A short and efficient synthetic access to functionalized compounds displaying major structural elements of the natural product populusone is elaborated by exploiting a diastereoselective Mukaiyama aldol addition followed by a triflic anhydride-induced oxa-Michael addition to construct the sensitive 2-oxa-bicyclo[2.2.2]octene unit as an enol triflate, which is directly used in a subsequent Suzuki cross-coupling. While attempts to close the strained 10-membered ring by means of Ru-catalyzed ring-closing metathesis were not successful, the developed synthetic scheme opens a rapid synthetic access to advanced intermediates, which may allow the completion of the total synthesis of populusone in the future.
Keywords: diterpenoids; Mukaiyama aldol reaction; 10-membered rings; oxa-Michael addition; Suzuki coupling; ring-closing metathesis